Establishment of Supervisory Institutions As an Effort to Fulfill Child Support Rights Due to Divorce - Ummu SALAMAH; Rachmi SULISTYARINI; Dhiana PUSPITAWATI (International Journal of Environmental, Sustainability, and Social Science, 2023)
The responsibility of parents to fulfill children's rights must still be carried out even if the parents are divorced. In Law Number 1 of 1974 concerning Marriage it is explained that the father is responsible for all rights to provide for the child, but often the father is negligent in fulfilling his obligations even though there has been a judge's decision in court. Basically in the realm of the Court, a request for execution can be made in fulfillment of child support costs if the father/ex-husband is negligent, but this execution is not an easy thing. The purpose of this study is to analyze the urgency of establishing a supervisory institution as an effort to fulfill child support costs due to divorce. This research method is normative law with statutory approaches, conceptual approaches, and comparisons originating from legal materials which are processed and analyzed with the results of the study.